2003
DOI: 10.1046/j.1365-2230.2003.01256.x
|View full text |Cite
|
Sign up to set email alerts
|

Onychomycosis due to Onychocola canadensis

Abstract: Onychocola canadensis is an uncommon nondermatophyte mould which can occasionally cause onychomycosis, and rarely, tinea manuum. It typically affects elderly individuals, some of whom have been farmers, in temperate climates. We describe a patient with onychomycosis due to this organism. She failed to respond to a 12-week course of terbinafine 250 mg o.d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…This fungus was described based on three isolates from Canadian cases of onychomycosis (Sigler & Congly 1990). Since then, cases in New Zealand (Sigler et al 1994), France (Contet-Audonneau et al 1997, Koenig et al 1997), Great Britain (Campbell et al 1997, O´Donoghue et al 2003), Italy (Fanti et al 2003, Belgium (Esbroeck et al 2003, Sijs et al 2007 and Spain (Torres-Sangiao et al 2006) have been reported. Recently, four cases were reported from Slovakia (Volleková & Lisalová 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This fungus was described based on three isolates from Canadian cases of onychomycosis (Sigler & Congly 1990). Since then, cases in New Zealand (Sigler et al 1994), France (Contet-Audonneau et al 1997, Koenig et al 1997), Great Britain (Campbell et al 1997, O´Donoghue et al 2003), Italy (Fanti et al 2003, Belgium (Esbroeck et al 2003, Sijs et al 2007 and Spain (Torres-Sangiao et al 2006) have been reported. Recently, four cases were reported from Slovakia (Volleková & Lisalová 2009).…”
Section: Introductionmentioning
confidence: 99%
“…34 In addition to these, two other groups reported phaeohyphomycosis of the ungual apparatus and onychomycosis due to Onychocola canadensis, which can be seen very rarely. 35,36 It is estimated to affect approximately 12% of the U.S. population. 37,38 According to 'Foot Check Study', the prevalence of onychomycosis among Germans is 12.4%.…”
Section: Onychomycosismentioning
confidence: 99%
“…In 1990 Sigler and Congly reported O. canadensis as a new agent of onychomycosis. A review of literature up to March 2013 gave 51 reported cases . In 2002, Gibas et al .…”
Section: Objectivesmentioning
confidence: 99%